Night stalkers 160th Special Operations Aviation Regiment (airborne) - Pushies, Fred J., 1952- (Zenith Press, 2005)
The 160th Special Operations Aviations Regiment specializes in carrying out its life-and-death operations under the cover of darkness, hence their nickname: "Night Stalkers." They are renowned for being swift, sure, and particularly deadly with their accuracy in using state-of-the-art aircraft and equipment to assist special ops from the air. Their specialty is covert insertion, re-supply, and extraction of Special Ops teams. They also take part in armed escort, reconnaissance, surveillance, and electronic warfare in support of missions.